Respuesta :
My answer to the problem is as follows:
1. Use the kinematic formula
Vf = Vi + a*t
for a, Vi = 3.0 m/s, a = 0.5 m/s/s, and t = 7.o s.
for b, Vf = 0, Vi = 3.0 m/s, and a = -0.60 m/s/s.
I hope my answer has come to your help. God bless and have a nice day ahead!
1. Use the kinematic formula
Vf = Vi + a*t
for a, Vi = 3.0 m/s, a = 0.5 m/s/s, and t = 7.o s.
for b, Vf = 0, Vi = 3.0 m/s, and a = -0.60 m/s/s.
I hope my answer has come to your help. God bless and have a nice day ahead!
Answer:
Part a)
[tex]v_f = 6.5 m/s[/tex]
Part b)
[tex]t = 5 seconds[/tex]
Explanation:
Part a)
As we know that
[tex]v_f = v_i + at[/tex]
here we know that
[tex]v_i = 3 m/s[/tex]
[tex]a = 0.5 m/s^2[/tex]
[tex]t = 7.0 s[/tex]
so we will have
[tex]v_f = 3 + (0.5)(7.0)[/tex]
[tex]v_f = 6.5 m/s[/tex]
Part b)
if finally the snowmobile comes to rest
So here we can say that
[tex]v_f = 0[/tex]
[tex]v_i = 3.0 m/s[/tex]
[tex]a = -0.60 m/s^2[/tex]
so now we have
[tex]v_f = v_i + at[/tex]
[tex]0 = 3.0 - (0.60)t[/tex]
[tex]t = 5 s[/tex]